Anti-obesity effect of n-3 polyunsaturated fatty acids in mice fed high-fat diet is independent of cold-induced thermogenesis - Janovská, P; Flachs, P; Kazdová, L; Kopecký, J (Physiological research, 2013)
Long-chain n-3 polyunsaturated fatty acids (LC n-3 PUFA) exert beneficial effects on health and they could help to prevent development of obesity and associated metabolic disorders. In our previous studies in mice fed high-fat (cHF; ~60 % calories as fat) diet and maintained at 20 °C, dietary LC n-3 PUFA could counteract accretion of body fat, without inducing mitochondrial uncoupling protein 1 (UCP1) in adipose tissue, suggesting that the anti-obesity effect was not linked to adaptive (UCP1-mediated) thermogenesis. To exclude a possible dependence of the anti-obesity effect on any mechanism inducible by cold, experiments were repeated in mice maintained at thermoneutrality (30 °C). Male C57BL/6J mice were fed either cHF diet, or cHF diet supplemented with LC n-3 PUFA, or standard diet for 7 months. Similarly as at 20 °C, the LC n-3 PUFA supplementation reduced accumulation of body fat, preserved lipid and glucose homeostasis, and induced fatty acid re-esterification in epididymal white adipose tissue. Food consumption was not affected by LC n-3 PUFA intake. Our results demonstrated anti-obesity metabolic effect of LC n-3 PUFA, independent of cold-induced thermogenesis and they suggested that induction of fatty acid re-esterification creating a substrate cycle in white fat, which results in energy expenditure, could contribute to the anti-obesity effect.
Keywords: obezita; tuková tkáň; Triglycerides; kyseliny mastné neesterifikované; Diet, High-Fat; termogeneze; nízká teplota; Anti-Obesity Agents; zvířata; omega-3 mastné kyseliny; myši; Fatty Acids, Omega-3; Glucose Tolerance Test; myši inbrední C57BL; Cold Temperature; Mice; glukózový toleranční test; triglyceridy; homeostáza; Male; nepřímá kalorimetrie; Homeostasis; Mice, Inbred C57BL; Calorimetry, Indirect; Fatty Acids, Nonesterified; dieta s vysokým obsahem tuků; Obesity; Body Weight; Animals; Thermogenesis; tělesná hmotnost; mužské pohlaví; látky proti obezitě; Adipose Tissue